2017
DOI: 10.1016/j.celrep.2016.12.052
|View full text |Cite
|
Sign up to set email alerts
|

CRTC1 Nuclear Translocation Following Learning Modulates Memory Strength via Exchange of Chromatin Remodeling Complexes on the Fgf1 Gene

Abstract: SUMMARY Memory is formed by synapse-to-nucleus communication that leads to regulation of gene transcription, but the identity and organizational logic of signaling pathways involved in this communication remain unclear. Here we find that the transcription factor CRTC1 is a critical determinant of sustained gene transcription and memory strength in the hippocampus. Following associative learning, synaptically localized CRTC1 is translocated to the nucleus and regulates Fgf1b transcription in an activity-depende… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
89
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 53 publications
3
89
0
Order By: Relevance
“…Both the focal deletion of HDAC3 in the CA subregion of hippocampus as well as HDAC3 inhibition via RGFP136 significantly enhances long-term memory (McQuown et al, 2011). Similarly, viral-mediated acute knockdown of HDAC3 in the CA subregion of the hippocampus or intra-hippocampal injection of an HDAC3 selective inhibitor leads to enhanced contextual fear memory (Uchida et al, 2017a). However, a prolonged HDAC3 depletion reduces memory (Nott et al, 2016).…”
Section: Epigenetic Mechanisms In Memory Formationmentioning
confidence: 99%
See 4 more Smart Citations
“…Both the focal deletion of HDAC3 in the CA subregion of hippocampus as well as HDAC3 inhibition via RGFP136 significantly enhances long-term memory (McQuown et al, 2011). Similarly, viral-mediated acute knockdown of HDAC3 in the CA subregion of the hippocampus or intra-hippocampal injection of an HDAC3 selective inhibitor leads to enhanced contextual fear memory (Uchida et al, 2017a). However, a prolonged HDAC3 depletion reduces memory (Nott et al, 2016).…”
Section: Epigenetic Mechanisms In Memory Formationmentioning
confidence: 99%
“…A recent paper has shown that KAT5 (also referred to as Tip60) plays a key role in learning-induced histone H4K12 acetylation, a potentially important lysine residue of histone H4 for memory (Guan et al, 2009; Peleg et al, 2010), and this mechanism is important for regulation of memory enhancement (Uchida et al, 2017a). …”
Section: Epigenetic Mechanisms In Memory Formationmentioning
confidence: 99%
See 3 more Smart Citations